2010
DOI: 10.2138/am.2010.3427
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of emission centers in alkali feldspar: A new approach by using cathodoluminescence spectral deconvolution

Abstract: Alkali feldspars in syenite from the Cerro Balmaceda pluton in the Patagonian Andes, Chile, show various petrographic microtextures formed during the magmatic to high-and low-temperature hydrothermal stages in which cathodoluminescence (CL) shows a wide range of blue, violet, and pink to red colors with variable brightness. Their CL spectra exhibit two emission bands: one at 405-420 nm in the blue region and the other at 700-760 nm in the red-infrared (IR) region. Asymmetrically shaped spectral peaks in energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 23 publications
1
63
2
Order By: Relevance
“…Unimplanted, He + -ionimplanted and electron irradiated anorthoclase and adularia have an emission band at ~420 nm in blue region (Figs. 2 and 4), which is activated by Ti 4+ impurity centers (Mariano et al, 1973;Finch and Klein, 1999;Götze et al, 2000;Lee et al, 2007;Parsons et al, 2008;Kayama et al, 2010). CL intensities of these UV and blue emissions decrease with increases in radiation dose of He + ion implantation and electron irradiation time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unimplanted, He + -ionimplanted and electron irradiated anorthoclase and adularia have an emission band at ~420 nm in blue region (Figs. 2 and 4), which is activated by Ti 4+ impurity centers (Mariano et al, 1973;Finch and Klein, 1999;Götze et al, 2000;Lee et al, 2007;Parsons et al, 2008;Kayama et al, 2010). CL intensities of these UV and blue emissions decrease with increases in radiation dose of He + ion implantation and electron irradiation time.…”
Section: Resultsmentioning
confidence: 99%
“…Highresolution CL images were observed using a Gatan: MiniCL imaging system under the same conditions as CL spectral analysis using SEM-CL. More details of the equipment construction and analytical procedures can be found in Ikenaga et al (2000) and Kayama et al (2010).…”
Section: Samples and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a spectral deconvolution should be required for the characterization of constituent emission components in zircon CL. Recently, Tsuchiya et al (2015) have demonstrated that a spectral deconvolution of natural zircon CL can be successfully carried out using a Gaussian function in energy units by the peak-fitting method proposed by Stevens-Kalceff (2009) and Kayama et al (2010). We deconvolute the CL spectra of unimplanted and He + -ion implanted samples with initial peak energies determined by Tsuchiya et al (2015) using the peak-fitting software (Peak Analyzer) implemented in Origin Pro 8.1J SR2.…”
Section: Of Synthetic Zirconmentioning
confidence: 99%